Association between body mass index and fragility fracture in postmenopausal women: a cross-sectional study using Korean National Health and Nutrition Examination Survey 2008-2009 (KNHANES IV) - Jihan Kim; Sami Lee; Sung Soo Kim; Jong-Pyo Lee; Jong Sung Kim; Jin Gyu Jung; Seok Jun Yoon; Kyu Pil Kim; Chan-Keol Park; Yong-Hwan Kim (BMC, 2021)
Abstract Background The present study examined the relationship between body mass index (BMI) and the risk for fragility fractures in postmenopausal Korean women. Methods Among subjects who participated in the 4th Korea National Health and Nutrition Examination Survey (2008-2009), 2114 women ≥ 40 years of age were included. BMI was based on standards set by the Korean Society for the Study of Obesity, as follows: < 18.5 kg/m2, underweight; 18.5 ≤ to < 25 kg/m2, normal weight; and ≥ 25 kg/m2, obese. Subjects were also divided into three groups according to the location of fragility fracture: spine, hip, or wrist. Results The mean (± SD) rate of fragility fracture was significantly different among the three groups: 5.9 ± 2.9% (underweight), 1.1 ± 0.3% (normal weight), and 3.0 ± 0.7% (obese) (p = 0.001). After correcting for age, family history, and treatment history of osteoporosis and rheumatoid arthritis, smoking and drinking status, and level of exercise, multivariable regression analysis revealed that the odds ratio for fragility fracture in the underweight group was 5.48 [95% confidence interval (CI) 1.80-16.73] and 3.33 (95% CI 1.61-6.87) in the obese group. After subdividing fragility fractures into vertebral and non-vertebral, the odds ratio for vertebral fracture in the underweight group was 5.49 (95% CI 1.31-23.09) times higher than that in the normal weight group; in the obese group, the non-vertebral fracture odds ratio was 3.87 (95% CI 1.45-10.33) times higher. Analysis of non-vertebral fractures in the obese group revealed an odds ratio for fracture 22.05 (95% CI 1.33-365.31) times higher for hip fracture and 3.85 (95% CI 1.35-10.93) times higher for wrist fracture. Conclusions Obesity and underweight increased the risk for fragility fractures in postmenopausal Korean women.